Actor Collaboration in Realizing New Zero Emission 2060 Through Renewable Energy Acceleration In South Sulawesi Province - Aslinda Aslinda; Muhammad Luthfi Siraj; Muh. Ikramullah Akmal (Universitas Negeri Makassar, 2023)
Actor collaboration in the implementation of renewable policies is very important to do to deal with climate change and to realize new zero emissions. This study aims to analyze the collaboration of actors in realizing new zero emissions by 2060 through accelerating renewable energy in South Sulawesi Province. The research method uses a qualitative approach. Data sources include primary and secondary data. The informants of this research are the stakeholders involved in the implementation of renewable energy policies. Data collection methods include observation, in-depth interviews and documentation as well as data analysis techniques using interactive data analysis methods. Apart from that, there is also a sectoral ego that is happening in the South Sulawesi government and also BUMN PLN partners who delegate budget allocations for the distribution of electric vehicles as well as political intervention that requires the electric vehicle program to be carried out by the party the government wants, which is different from the wishes of the government. other partners. On the other hand, the findings of this study also found that the collaboration of government actors and the private sector did not provide clear certainty regarding the financial and non-financial benefits that could be obtained by investors and the community when the electric vehicle program was fulfilled for use by the people in South Sulawesi.